Rise Of Islam In Kashmir Valley - Shabir Ahmad Lone; Mohammad Ishaq Lone (PT. Radja Intercontinental Publishing, 2026)
Kashmiri Muslims are ethnic Kashmiris who practice Islam and are native to the Kashmir Valley in Indian-administered Kashmir.Sunni Muslims represent almost all of Kashmiri Muslims. They call themselves